IMPLEMENTASI PENDIDIKAN MULTIKULTURAL BERBASIS ISLAM RAHMATAN LIL ALAMIN DALAM MEWUJUDKAN MADRASAH INKLUSIF DI MTS HIDAYATUL ISLAMIYAH BUMIREJO BOJONEGORO - Wahyu Gilang Romadhon; Sauqi Futaqi; Saefrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to describe the implementation of multicultural education based on the *Islam Rahmatan lil 'Alamin* (Islam as a mercy to the worlds) paradigm in establishing an inclusive *madrasah* at MTs Hidayatul Islamiyah Bumirejo. Employing a descriptive qualitative approach, the study gathered data through observation, in-depth interviews, and documentation involving the *madrasah* principal, teachers, and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that multicultural education is implemented through instructional planning and delivery that integrate values ​​of tolerance, justice, cooperation, and respect for diversity. Furthermore, the cultivation of *madrasah* culture, religious activities, and harmonious social interactions supports the creation of a humanistic and non-discriminatory environment. This implementation contributes to realizing an inclusive *madrasah* characterized by equal learning opportunities, respect for differences, a culture of mutual cooperation (*gotong royong*), and the prevention of discrimination and bullying. Thus, multicultural education based on *Islam Rahmatan lil 'Alamin* is effective in shaping an inclusive, tolerant *madrasah* grounded in the values ​​of moderate Islam